Numerical Solution of the Effect of Increasing the Wall Temperature on Flow and Heat Transfer in Pulsating Heat Pipe - Habiballah Sayevand; Reza Nemati (مجله مدل سازی در مهندسی, 2020)
In this paper the effects of increasing the wall temperature and the amount of liquid charge on the oscillating flow in a U-shaped miniature tube, with a simple bend of diameter 1.5 mm and closed end investigated. The governing equations are obtained by applying the conservation of mass, momentum and energy for the liquid slug and the vapor plugs. A complete numerical simulation has been performed to investigate the effects of wall temperature and the amount of liquid charge on the heat pipe performance using explicit method. The obtained results show that by increasing the walls temperature difference, amplitude of oscillations of the liquid slug, sensible and latent heat transfer will be increased, as the temperature difference is increased by only ,oscillation amplitude of the liquid slug about 8 mm, the sensible heat transfer 4 watts and the latent heat transfer watts increases. Additionally, by increasing the charge rate, the oscillation amplitude and the sensible heat transfer are significantly reduced, for example, increasing the charge rate from 30 to 50% reduces the oscillation amplitude by about 65 mm as well as the sensible heat transfer by 87 watts reduces. In the charging ratio 90%, the heat pipe operation is stopped.